Effect of Metal Dopant on Ninhydrin—Organic Nonlinear Optical Single Crystals - R. S. Sreenivasan; N. Kanagathara; G. Ezhamani; N. G. Renganathan; G. Anbalagan (Journal of Spectroscopy)
In the present work, metal (Cu2+)-substituted ninhydrin single crystals were grown by slow evaporation method. The grown crystals have been subjected to single crystal XRD, powder X-ray diffraction, FTIR, dielectric and SHG studies. Single crystal X-ray diffraction analysis reveals that the compound crystallizes in monoclinic system with noncentrosymmetric space group P21 with lattice parameters a=11.28 Å, b=5.98 Å, c=5.71 Å, α=90∘, β=98.57, γ=90∘, and V=381 (Å)3, which agrees very well with the reported value. The sharp and strong peaks in the powder X-ray diffraction pattern confirm the good crystallinity of the grown crystals. The presence of dopants marginally altered the lattice parameters without affecting the basic structure of the crystal. The UV-Vis transmittance spectrum shows that the crystal has a good optical transmittance in the entire visible region with lower cutoff wavelength 314 nm. The vibrational frequencies of various functional groups in the crystals have been derived from FT-IR analysis. Based on the shifts in the vibrations, the presence of copper in the lattice of the grown crystal is clearly established from the pure ninhydrin crystals. Both dielectric constant and dielectric loss decrease with the increase in frequency. The second harmonic generation efficiency was measured by employing powder Kurtz method.